Analyzing post-colonial impacts of external interventions on Africa’s national and regional integration - Admasu, Embiale Beyene; Chekol, Yayew (Política. Revista de Ciencia Política, 2024)
The most intention of this paper is investigating the impacts of Post-Colonial External interventions in Africa’s national and regional integration. The researchers employed qualitative research approach, and used secondary sources of data lastly thematic analysis technique was used. The paper addressed that external interventions through the lenses of history are not conducive for Africa’s integrations. Though there is change of superpowers across time, Africa’s place is the same-raw material supplier and market for dumping. The external interventions remain key challenges of the Africa’s prospects for harmonization of state-society relations and ensuring regional integrations. External forces do continue in undermining Africa’s long awaited aspiration for the establishment of United States of Africa. Any intervening foreign power, therefore, brings with its own interests, its own political value system, and could limit the success of Africa’s integration. Addressing the root causes of problem not only to bring an end to existing functionality problems, but also to prevent new cycles of failure. The focus should be on building good state society relations and design¬ing and implementing integration agenda across levels, strengthening regional integration at any cost possible, and take positive lessons from the past and present external interventions.